CHARACTERIZATION AND DETERMINATION OF OCA'S(OXALIS TUBEROSA) ECOTYPES, OR FLOUR PROCESSING IN THE ANCASH RAVINE, DISTRICT AND PROVINCE OF YUNGAY, ANCASH REGION. - Yenque Dedios, Julio (2007)
The country has inmumerable nutrional natural resources of Andean Character, one of which is oca, which not yet has taken advantage of and amassed its consumption; reason for which this study raises to make an analysis of the types of oca which they exist in the mountain range of the Ancash region, determining its physical and chemical characteristics for its later recommendation, dentroi of a contex of an industrialization possibility. In order to fulfill this assignment, professional efforts and of field have come together. In this sense it has been possible the participation of the university through his laboratories of the university through his laboratories and Centers of Processing, education and independent, producing investigators of oca population in general, with the purpose of making tests of laboratory for the obtaining of flour and nectar.